Exploring the role of large synthons in the design of bicomponent salts of cimetidine - Khatun, Saheba; Sar, Bandana; Hosmani, Girish Siddanagouda; Mishra, Manish Kumar; Ravi, Punna Rao; Mukherjee, Arijit (Crystal Growth & Design, 2026)
Cimetidine, a popular histamine H2-receptor antagonist, represents a complex structural landscape exhibiting multiple forms. Attempts to synthesize a bicomponent salt with fumaric acid suffered from crystallization challenges in the past, especially toward the growth of anhydrous single crystals. In this work, we address these crystallization challenges by adopting an alternative crystallization approach involving ionic liquids and analyzing the structural landscape with a large synthon-based approach. Two novel forms of cimetidine fumarate were isolated. The structural differences in the forms of cimetidine fumarate were further explored by using different coformers as structural probes.